Composite proton exchange membrane as well as preparation method and application thereof
By functionalizing porous silicon in organic phosphonic acid with polymer matrix and phosphoric acid, a composite high-temperature proton exchange membrane is solved, and the problem of difficult improvement in the proton conduction performance and battery performance of existing high-temperature proton exchange membrane fuel cells under high temperature conditions is solved. It achieves efficient proton conduction and phosphoric acid retention, improving the stability and performance of fuel cells.
Patent Information
- Application Number
- CN202310952142.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing high-temperature proton exchange membrane fuel cells have problems such as low environmental adaptability, low utilization efficiency of precious metal catalysts, high cost and complex hydrothermal management systems. The proton conduction performance and battery performance of the phosphate-based proton exchange membrane under high temperature conditions are difficult. It is improved, and the problem of phosphoric acid loss is difficult to overcome.
Organophosphonic acid functionalized porous silicon material is used to recombine with polymer matrix and phosphoric acid to form a composite high-temperature proton exchange membrane. Organophosphonic acid functionalized porous silicon itself has proton conduction ability, and through combination with polymer matrix and phosphoric acid, the proton conduction performance and phosphoric acid retention ability are improved.
A composite proton exchange membrane with high proton conductivity and strong phosphoric acid retention ability in the range of 100 to 200°C is achieved, which improves the operating stability and battery performance of the fuel cell.
Smart Images

Figure CN119447392A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite proton exchange membrane and a preparation method and application thereof, belonging to the fields of new material technology and new energy technology. Background Art
[0002] Proton exchange membrane fuel cells with proton exchange membrane as electrolyte have the characteristics of high energy conversion efficiency, low operating temperature, fast start-up and long life. They can be widely used as power sources for vehicles and fixed power stations. They are the fuel cells with the most promising commercial applications. At present, proton exchange membrane fuel cells have problems such as low environmental adaptability, low utilization efficiency of precious metal catalysts, high cost and complex water thermal management system. It is generally believed that increasing the operating temperature of fuel cells is an effective countermeasure to solve these problems. When the operating temperature of proton exchange membrane fuel cells is increased above 100℃, the battery reaction kinetics will increase, the catalytic efficiency of Pt catalyst will increase, and the amount of Pt catalyst used can be greatly reduced; and the tolerance of Pt catalyst to CO also increases exponentially with temperature; at the same time, increasing the operating temperature will reduce the battery's requirements for water thermal management system. However, too high a temperature (above 500℃) will place more stringent requirements on the component materials of proton exchange membrane fuel cells. Therefore, it is of great significance to develop high-temperature (100-500℃) proton exchange membrane fuel cells. The most important challenge in developing high-temperature proton exchange membrane fuel cells is to develop high-temperature proton exchange membranes with superior performance.
[0003] In view of the unique advantages of high-temperature proton exchange membrane fuel cells, research on high-temperature proton exchange membranes has become a hot topic. Among them, phosphate-based proton exchange membranes have attracted widespread attention due to their relatively good proton conductivity under high temperature conditions, but further improvements in their proton conductivity and battery performance are difficult to achieve, and the loss of phosphoric acid has been difficult to overcome. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides an organic phosphonic acid functionalized porous silicon doped polymer composite high temperature proton exchange membrane and its preparation method and application, which are mainly used in high temperature (100-200°C) fuel cells. The composite high temperature proton exchange membrane is composed of organic phosphonic acid functionalized porous silicon, polymer matrix and phosphoric acid, with organic phosphonic acid functionalized porous silicon as an added component and polyaryl polymer as a matrix. The organic phosphonic acid functionalized porous silicon is a porous silicon material modified by organic phosphonic acid. Organic phosphonic acid carries phosphoric acid groups, which are assembled with porous silicon into a highly ordered electrolyte structure. Therefore, the organic phosphonic acid functionalized porous silicon itself has proton conduction ability, and the porous silicon itself has a large pore size, which can accommodate organic phosphonic acid groups. In addition, the crystal size is at the nanometer level, which can provide abundant surface area, act as a carrier and skeleton, and is a good water and acid retention material. Introducing the organic phosphonic acid functionalized porous silicon in the present invention into the polymer can not only improve the proton conduction performance, but also reduce the loss of phosphoric acid and improve the battery operation stability. The obtained composite proton exchange membrane is extremely dense and has strong proton conductivity.
[0005] The present invention provides an organic phosphonic acid functionalized porous silicon doped polymer composite proton exchange membrane and its preparation method and application, which are mainly used in high temperature (100-200°C) fuel cells. The composite proton exchange membrane is composited by organic phosphonic acid functionalized porous silicon material, polymer matrix and phosphoric acid. The organic phosphonic acid functionalized porous silicon is a porous silicon material modified by organic phosphonic acid.
[0006] According to one aspect of the present application, a composite proton exchange membrane is provided, wherein the composite proton exchange membrane is composited with an organic phosphonic acid functionalized porous silicon material and a polymer matrix and is soaked in phosphoric acid;
[0007] The organic phosphonic acid functionalized porous silicon material is porous silicon modified by organic phosphonic acid;
[0008] The polymer matrix is selected from at least one of polysulfone, polyetheretherketone, polyimide, polybenzimidazole and polyphenylene sulfide sulfone.
[0009] Optionally, the porous silicon is selected from at least one of SBA-15, MCM-41, and amorphous porous silicon; and the particle size of the porous silicon is nanometer scale.
[0010] Optionally, the mass ratio of the organic phosphonic acid functionalized porous silicon material to the polymer matrix is 1:5-20.
[0011] Optionally, the mass ratio of the organic phosphonic acid functionalized porous silicon material to the polymer matrix is selected from any value of 1:5, 1:6, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20 or a range between any two of the above values.
[0012] According to another aspect of the present application, a method for preparing the composite proton exchange membrane described above is provided, the preparation method comprising the following steps:
[0013] (1) preparing organic phosphonic acid functionalized porous silicon material;
[0014] (2) mixing the organic phosphonic acid functionalized porous silicon material with a polymer matrix solution, casting, and drying to obtain a film-forming material;
[0015] (3) Soaking the membrane-forming material in phosphoric acid to obtain the composite proton exchange membrane.
[0016] Optionally, the method for preparing the organic phosphonic acid functionalized porous silicon material comprises:
[0017] In an inactive atmosphere, a mixture containing porous silicon, a silane coupling agent and a solvent is reacted I, and the obtained product is reacted II with other substances to obtain the organic phosphonic acid functionalized porous silicon material.
[0018] Optionally, the method for preparing the organic phosphonic acid functionalized porous silicon doped polymer composite proton exchange membrane comprises the following steps:
[0019] (1) Organic phosphonic acid functionalized porous silicon materials were prepared by the following three methods:
[0020] The first preparation method: first, add porous silicon powder to a round-bottom flask, add toluene, and disperse it evenly by ultrasonication; then add the organic silane coupling agent trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane (EHTMS), pass nitrogen protection, heat and reflux at 60-100°C for 6-36 hours; cool to room temperature, wash the solid product with toluene and ethanol several times, and then dry overnight. Then add it to a round-bottom flask, add aminotrimethylenephosphoric acid (ATMP), heat and reflux at 40-90°C for 6-36 hours; after cooling to room temperature, wash the solid product with ethanol several times, and dry overnight to obtain the final product;
[0021] The second preparation method: first, add the porous silicon powder to a round-bottom flask, add toluene, and disperse it evenly by ultrasonication; then add diethylphosphoethyltriethoxysilane (DPTS), pass nitrogen protection, heat and reflux at 60-100°C for 6-36 hours; cool to room temperature, wash the solid product with toluene and ethanol several times, and then dry overnight. Then add it to a round-bottom flask, add hydrochloric acid, heat and reflux at 40-90°C for 6-36 hours; after cooling to room temperature, wash the solid product with ethanol several times, and dry overnight to obtain the final product;
[0022] The third preparation method: add porous silicon powder to a round-bottom flask, add toluene, and disperse it evenly with ultrasound; then add 3-aminopropyltriethoxysilane (APTES), pass nitrogen protection, heat and reflux at 60-100°C for 6-36 hours; cool to room temperature, wash the solid product with toluene and ethanol several times, and then dry overnight. Then add it to a round-bottom flask, add formaldehyde and phosphorous acid successively, heat and reflux at 40-90°C for 6-36 hours; after cooling to room temperature, wash the solid product with ethanol several times, and dry overnight to obtain the final product;
[0023] (2) mixing the organic phosphonic acid functionalized porous silicon with a polymer matrix solution to form a film;
[0024] (3) The membrane is immersed in phosphoric acid to obtain a composite proton exchange membrane.
[0025] Optionally, in step (2), the organic phosphonic acid functionalized porous silicon and the polymer matrix solution are formed into a film by a tape casting method.
[0026] Optionally, the proton conductor is mixed with a polymer matrix solution to obtain a mixture, the mixture is ultrasonically treated for 2 to 4 hours to obtain a membrane-forming solution, the membrane-forming solution is placed on a glass plate, and dried at 55 to 65° C. to obtain the membrane; the sum of the mass fractions of the polymer matrix and the organic phosphonic acid functionalized porous silicon material is 2.5 to 5%.
[0027] Optionally, the porous silicon is selected from at least one of SBA-15, MCM-41, and amorphous porous silicon.
[0028] Optionally, the silane coupling agent is selected from one of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, diethylphosphoethyltriethoxysilane, and 3-aminopropyltriethoxysilane.
[0029] Optionally, the other substances are selected from at least one of aminotrimethylenephosphoric acid, hydrochloric acid, formaldehyde and phosphorous acid.
[0030] Optionally, the inert atmosphere is selected from at least one of nitrogen, argon and helium.
[0031] Optionally, when the silane coupling agent is trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, the other substance is aminotrimethylenephosphonic acid.
[0032] Optionally, when the silane coupling agent is diethylphosphoethyltriethoxysilane, the other substance is hydrochloric acid.
[0033] Optionally, when the silane coupling agent is 3-aminopropyltriethoxysilane, the other substances are formaldehyde and phosphorous acid.
[0034] Optionally, the mass ratio of the porous silicon to the silane coupling agent is 1:2-10.
[0035] Optionally, the mass volume ratio of the porous silicon to the solvent toluene is 5 to 15 mg / mL.
[0036] Optionally, the mass volume ratio of the porous silicon to the other substances is 0.1 to 1:1 g / mL.
[0037] Optionally, the temperature of the reaction I is 60-100° C., and the time of the reaction I is 6-36 hours.
[0038] Optionally, the temperature of the reaction I is selected from any value of 60°C, 70°C, 80°C, 90°C, 100°C or a range between any two of the above values.
[0039] Optionally, the reaction time I is selected from any value among 6h, 12h, 18h, 24h, 30h, 36h or a range between any two of the above.
[0040] Optionally, the temperature of the reaction II is 40° C. to 90° C., and the time of the reaction II is 6 to 36 hours.
[0041] Optionally, the temperature of the reaction II is selected from any value of 40°C, 60°C, 70°C, 80°C, 90°C or a range between any two of the above values.
[0042] Optionally, the time of reaction II is selected from any value among 6h, 12h, 18h, 24h, 30h, 36h or a range between any two of the above.
[0043] Optionally, the solvent in the polymer matrix solution is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone and acetone.
[0044] Optionally, the sum of the mass fractions of the polymer matrix and the organic phosphonic acid functionalized porous silicon material is 2.5-5%.
[0045] Optionally, in step (2), the drying temperature is 55 to 65° C., and the drying time is 12 to 60 hours.
[0046] Optionally, the drying temperature is selected from any value of 55°C, 58°C, 60°C, 62°C, 65°C or a range between any two of the above values.
[0047] Optionally, the drying time is selected from any value among 12h, 18h, 24h, 30h, 36h, 48h, 60h or a range between any two of the above.
[0048] Optionally, in step (3), the soaking temperature is 60 to 100° C., and the soaking time is 2 to 4 days.
[0049] Optionally, the soaking temperature is selected from any value of 60°C, 70°C, 80°C, 90°C, 100°C or a range between any two of the above values.
[0050] Optionally, the soaking time is selected from any value among 2 days, 2.5 days, 3 days, 3.5 days, 4 days, or a range between any two of the above.
[0051] According to another aspect of the present application, there is provided a use of the above-mentioned composite proton exchange membrane in a fuel cell.
[0052] Optionally, the operating temperature of the composite proton exchange membrane is 100-200°C.
[0053] The composite proton exchange membrane has a high proton conductivity at 100-200°C and a strong phosphate retention capacity, and the battery based on the membrane assembly can also operate stably at 100-200°C.
[0054] The beneficial effects of this application include:
[0055] The composite high-temperature proton exchange membrane provided by the present invention has the following advantages: organic phosphonic acid functionalized porous silicon is used as an added component, and a polyaryl polymer is used as a matrix. Organic phosphonic acid carries its own phosphoric acid group, which is assembled with porous silicon into a highly ordered electrolyte structure. Therefore, the organic phosphonic acid functionalized porous silicon itself has the ability to conduct protons, and the porous silicon itself has a large pore size, which can accommodate the organic phosphonic acid groups. In addition, the crystal size is at the nanoscale, which can provide abundant surface area, play the role of carrier and skeleton, and is a good water-retaining and acid-retaining material. Introducing the organic phosphonic acid functionalized porous silicon in the present invention into the polymer can not only improve the proton conduction performance, but also reduce the loss of phosphoric acid and improve the stability of battery operation. The resulting composite proton exchange membrane is extremely dense and has a strong proton conduction ability.
[0056] The present invention uses organic phosphonic acid functionalized porous silicon material as the doping material in the polymer membrane, which can not only improve the water and acid retention performance of the composite membrane, but also improve the proton conduction activity and high-temperature battery performance of the composite membrane. Compared with the prior art, the phosphoric acid-doped organic phosphonic acid functionalized porous silicon-doped polymer composite high-temperature proton exchange membrane prepared by the present invention has a higher proton conductivity at 100-200°C and a stronger phosphoric acid retention capacity, and the battery based on the membrane assembly can operate stably at 100-200°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1This is a 5um scanning electron microscope image of the organic phosphonic acid functionalized SBA-15 in Example 1 of the present application.
[0058] Figure 2 This is a full-cell performance test diagram of the high-temperature proton exchange membrane in Example 3, Comparative Example 3 and Comparative Example 4 of the present application. DETAILED DESCRIPTION
[0059] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0060] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0061] The proton conductivity of the membrane was measured using an electrochemical workstation.
[0062] The phosphate retention rate of the membrane was measured using a high-precision balance.
[0063] A customized high-temperature fuel cell test bench is used to measure the full cell performance of the high-temperature proton exchange membrane.
[0064] In the examples of the present application, room temperature refers to "25°C".
[0065] Example 1
[0066] 1) Add 1g of SBA-15 powder to a round-bottom flask, add 200mL of toluene, and disperse evenly by ultrasonication; then add 5g of an organic silane coupling agent, trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane (EHTMS), pass nitrogen protection, and heat at 80°C for 28 hours; cool to room temperature, wash the solid product with toluene and ethanol several times, and then dry overnight. Then add it to a round-bottom flask, add 2mL of aminotrimethylenephosphonic acid (ATMP), and heat at 80°C for 12 hours; after cooling to room temperature, wash the solid product with ethanol several times, and after drying overnight, obtain an organic phosphonic acid functionalized SBA-15 material, which is recorded as ATEHS15. Figure 1 This is a scanning electron micrograph of SBA-15 functionalized with organic phosphonic acid.
[0067] 2) The prepared ATEHS15 was mixed with a polyimide solution (mass fraction 2.5%), the mass ratio of ATEHS15 to polyimide was 1:10, the obtained mixture was ultrasonically treated for 3 hours to obtain a film-forming solution, the film-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 24 hours to obtain a membrane material.
[0068] 3) Soaking in phosphoric acid to obtain a composite proton exchange membrane doped with phosphoric acid. The obtained membrane material was soaked in phosphoric acid at 80°C for 3 days to obtain a composite proton exchange membrane PA-ATEHS15-PI. The basic physical properties of the membrane were measured and shown in Table 1.
[0069] Comparative Example 1
[0070] Polyimide solution (mass fraction 2.5%) was used as a membrane-forming liquid, placed on a glass plate, and kept in an oven at 60°C for 24 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid at 80°C for 3 days to obtain PA-PI. The basic physical properties of the membrane were measured and shown in Table 1.
[0071] Example 2
[0072] 1) Add 1g MCM-41 powder to a round-bottom flask, add 400mL toluene, and disperse evenly by ultrasonication; then add 3g 3-aminopropyltriethoxysilane (APTES), pass nitrogen protection, heat and reflux at 60°C for 6 hours; cool to room temperature, wash the solid product with toluene and ethanol several times, and then dry overnight. Then add to a round-bottom flask, add 3g formaldehyde and 2g phosphorous acid successively, and heat and reflux at 40°C for 36 hours; after cooling to room temperature, wash the solid product with ethanol several times, and dry overnight to obtain an organic phosphonic acid functionalized MCM-41 material, recorded as APM41.
[0073] 2) The prepared APM41 was mixed with a polysulfone solution (mass fraction 2.5%), the mass ratio of APM41 to polysulfone was 1:15, the obtained mixture was ultrasonically treated for 3 hours to obtain a membrane-forming solution, the membrane-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 48 hours to obtain a membrane material.
[0074] 3) Soaking in phosphoric acid to obtain a composite proton exchange membrane doped with phosphoric acid. The obtained membrane material was soaked in phosphoric acid at 60°C for 4 days to obtain a composite proton exchange membrane PA-APM41-PSF. The basic physical properties of the membrane were measured and shown in Table 1.
[0075] Comparative Example 2
[0076] Polysulfone solution (mass fraction 2.5%) was used as a membrane-forming liquid, placed on a glass plate, and kept in an oven at 60°C for 48 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid at 60°C for 4 days to obtain PA-PSF. The basic physical properties of the membrane were measured and shown in Table 1.
[0077] Example 3
[0078] 1) Add 1g of SBA-15 powder to a round-bottom flask, add 300mL of toluene, and disperse evenly by ultrasonication; then add 5g of diethylphosphoethyltriethoxysilane (DPTS), pass nitrogen protection, and heat and reflux at 90°C for 36 hours; cool to room temperature, wash the solid product with toluene and ethanol several times, and then dry overnight. Then add it to a round-bottom flask, add hydrochloric acid, and heat and reflux at 90°C for 18 hours; after cooling to room temperature, wash the solid product with ethanol several times, and dry overnight to obtain an organic phosphonic acid functionalized SBA-15 material, recorded as DPS15.
[0079] 2) The prepared DPS15 was mixed with a polybenzimidazole solution (mass fraction 2.5%), the mass ratio of DPS15 to polybenzimidazole was 1:5, the obtained mixture was ultrasonically treated for 3 hours to obtain a film-forming solution, the film-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 48 hours to obtain a membrane material.
[0080] 3) The obtained membrane material was immersed in phosphoric acid at 100° C. for 2 days to obtain a composite proton exchange membrane PA-DPS15-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0081] Comparative Example 3
[0082] 1) SBA-15 powder and polybenzimidazole solution (mass fraction 2.5%) were mixed, the mass ratio of SBA-15 powder to polybenzimidazole was 1:5, the obtained mixture was ultrasonically treated for 3 hours to obtain a film-forming solution, the film-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 48 hours to obtain a membrane material.
[0083] 2) The obtained membrane material was immersed in phosphoric acid at 100° C. for 2 days to obtain a composite proton exchange membrane PA-S15-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0084] Comparative Example 4
[0085] Polybenzimidazole solution (mass fraction 2.5%) was used as a membrane-forming liquid, placed on a glass plate, and kept in an oven at 60°C for 48 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid at 100°C for 2 days to obtain PA-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0086] The composite high temperature proton exchange membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to charge and discharge experiments, and the basic physical properties of the membranes were measured and shown in Table 1.
[0087] Table 1
[0088]
[0089] Compared with Example 3, the added material in Comparative Example 3 is SBA-15 powder that is not functionalized with organic phosphonic acid, and the other compositions and parameters are the same; Comparative Example 4 does not contain any added components, and the other compositions and parameters are the same. Figure 2As shown, by comparing Example 3 with Comparative Examples 3 and 4, it can be seen that the introduction of organic phosphonic acid functionalized SBA-15 in the present invention plays an important role in improving the conductivity of the composite membrane, battery performance and phosphoric acid retention rate. Organic phosphonic acid has its own phosphate group, which is assembled with SBA-15 into a highly ordered electrolyte structure. Therefore, organic phosphonic acid functionalized SBA-15 itself has proton conductivity. At the same time, the SBA-15 crystal size in the present invention is small, the specific surface area is large, and it is a better water-retaining and acid-retaining material, which makes an important contribution to improving the phosphoric acid retention rate. Therefore, in the present invention, the introduction of organic phosphonic acid gives SBA-15 proton conductivity, and the acid retention capacity of SBA-15 increases the amount of phosphoric acid introduced into the composite membrane, which together improves the conductivity and battery performance of the material.
[0090] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A composite proton exchange membrane, characterized in that: The composite proton exchange membrane is composited by organic phosphonic acid functionalized porous silicon material and polymer matrix and soaked in phosphoric acid; The organic phosphonic acid functionalized porous silicon material is porous silicon modified by organic phosphonic acid; The polymer matrix is selected from at least one of polysulfone, polyetheretherketone, polyimide, polybenzimidazole and polyphenylene sulfide sulfone.
2. The composite proton exchange membrane according to claim 1, characterized in that: The porous silicon is selected from at least one of SBA-15, MCM-41, and amorphous porous silicon; the particle size of the porous silicon is nanometer scale; Preferably, the mass ratio of the organic phosphonic acid functionalized porous silicon material to the polymer matrix is 1:5-20.
3. The method for preparing a composite proton exchange membrane according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: (1) preparing organic phosphonic acid functionalized porous silicon material; (2) mixing the organic phosphonic acid functionalized porous silicon material with a polymer matrix solution, casting, and drying to obtain a film-forming material; (3) Soaking the membrane-forming material in phosphoric acid to obtain the composite proton exchange membrane.
4. The preparation method according to claim 3, characterized in that: The preparation method of the organic phosphonic acid functionalized porous silicon material comprises: In an inactive atmosphere, a mixture containing porous silicon, a silane coupling agent, and a solvent is subjected to a reaction I, and the obtained product is then reacted with other substances II to obtain the organic phosphonic acid functionalized porous silicon material; Preferably, the porous silicon is selected from at least one of SBA-15, MCM-41, and amorphous porous silicon; Preferably, the silane coupling agent is selected from one of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, diethylphosphoethyltriethoxysilane, and 3-aminopropyltriethoxysilane; Preferably, the other substances are selected from at least one of aminotrimethylenephosphoric acid, hydrochloric acid, formaldehyde and phosphorous acid.
5. The preparation method according to claim 4, characterized in that: When the silane coupling agent is trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, the other substance is aminotrimethylenephosphoric acid; Preferably, when the silane coupling agent is diethylphosphoethyltriethoxysilane, the other substance is hydrochloric acid; Preferably, when the silane coupling agent is 3-aminopropyltriethoxysilane, the other substances are formaldehyde and phosphorous acid.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the porous silicon to the silane coupling agent is 1:2-10; Preferably, the mass volume ratio of the porous silicon to the other substances is 0.1 to 1:1 g / mL; Preferably, the temperature of the reaction I is 60 to 100° C., and the time of the reaction I is 6 to 36 hours; Preferably, the temperature of the reaction II is 40° C. to 90° C., and the time of the reaction II is 6 to 36 hours.
7. The preparation method according to claim 3, characterized in that: The solvent in the polymer matrix solution is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone and acetone; Preferably, the sum of the mass fractions of the polymer matrix and the organic phosphonic acid functionalized porous silicon material is 2.5-5%.
8. The preparation method according to claim 3, characterized in that: In the step (2), the drying temperature is 55 to 65° C. and the drying time is 12 to 60 hours; Preferably, in step (3), the soaking temperature is 60 to 100° C., and the soaking time is 2 to 4 days.
9. Use of the composite proton exchange membrane according to any one of claims 1 to 2 in a fuel cell.
10. The use according to claim 9, characterized in that: The working temperature of the composite proton exchange membrane is 100-200°C.
Citation Information
Patent Citations
Preparation method for phosphoric-acid-group functionalized hollow mesoporous silica microsphere
CN107970878A
Composite high-temperature proton exchange membrane as well as preparation and application thereof
CN108183250A
Crosslinking composite organic phosphonate high-temperature proton exchange membrane and preparation method thereof
CN108832161A
Fiber-reinforced polymer composite electrolyte membrane functionalized with hydrogen ion-transferring functional group of ceramic fiber
KR1020140080730A
Novel compositions of monomers, oligomers and polymers and methods for making the same
US20060088748A1